The Effect Of Brand Identıty And Perceıved Qualıty On Brand Posıtıonıng Of Courıer Servıces PT Pos Indonesıa (Persero) Maın Branch, Semarang Cıty - Riyadi Riyadi; Arif Anom Septyawan; M Nahar; Saptianing Saptianing; Sri Wahyuni; Rara Ririn B.U (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
In the current era, the need for inter-regional shipping is increasingly needed. The presence of courier services helps people in shipping goods between regions. PT Pos Indonesia as a state-owned company has a courier service that serves delivery of goods or documents between regions and even between countries. The results of a survey conducted on the Top Brand Index in 2020, PT Pos ranks 4th out of 5 companies that were used as research objects. This study aims to determine the effect of brand identity and perceived quality on brand positioning in the courier service of PT Pos Indonesia (Persero) Main Branch of Semarang City. The sample used in this study was 100 respondents using accidental sampling technique. Data collection instrument with a questionnaire that has been tested for validity and reliability. Analysis of the data used in this study using multiple linear regression analysis. The test results of multiple regression analysis show that brand identity and perceived quality have a significant effect on brand positioning. The regression model is the best fit model where brand identity and perceived quality contribute 66.6% to brand positioning. To increase PT Pos's Top Brand Index, it is recommended to focus on increasing the indicators of memorability, features and suitability.